Neuroform atlas stent-assisted coiling of tiny wide-necked intracranial aneurysms - Dong, Linggen; Chen, Xiheng; Wang, Jiejun; Zhang, Longhui; Zhao, Zhiqiang; Peng, Qichen; Liu, Peng; Lv, Ming (Frontiers in Neurology, 2022)
Objective To investigate the safety and efficacy of Neuroform Atlas stent-assisted coiling for the treatment of tiny wide-necked intracranial aneurysms and evaluate risk factors associated with procedure-related complications. Methods We retrospectively examined 46 patients with 46 tiny wide-necked aneurysms who were treated using Atlas stent-assisted coiling at our institution from August 2020 to May 2022. Patient and aneurysm characteristics, procedural details, procedure-related complications, and angiographic and clinical outcomes were analyzed. Results A total of 10 patients presented with aneurysmal rupture. Atlas stent placement was successful in all patients. Angiography immediately after the procedure showed complete occlusion in 38 patients (82.6%), neck remnant in 7 (15.2%), and partial occlusion in 1 (2.2%). The mean angiographic follow-up was 8.4 months (range, 6–16). At the last follow-up, angiography showed complete occlusion in 41 patients (89.1%) and neck remnant in 5 (10.9%). No aneurysm recurrence or in-stent stenosis occurred. Incidence of procedure-related complications was 10.8% (intraprocedural aneurysm rupture, two cases; acute thrombosis, two cases; and coil migration, one case); only one patient (2.2%) experienced procedural neurological morbidity. The mean clinical follow-up was 9.7 months. A favorable outcome was achieved in 45 patients (97.8%). In univariate logistic regression analysis, aneurysm size (odds ratio, 4.538; P = 0.045) was significantly associated with procedure-related complications. However, multivariate analysis found no independent risk factors. Conclusion Atlas stent-assisted coiling of tiny wide-necked intracranial aneurysms is feasible and effective. Outcomes and occlusion rates are favorable and morbidity is low. The complication rate may be higher in larger tiny aneurysms.